Morphology and composition of Goldeye (Hiodontidae; Hiodon alosoides) otoliths. (1st February 2021) - Long, James M.; Snow, Richard A.; Pracheil, Brenda M.; Chakoumakos, Bryan C.
Abstract: We provide up‐to‐date morphological and compositional data on otoliths of the osteoglossomorph Goldeye ( Hiodon alosoides ). Using computed tomography (CT) X‐ray, we documented the location of each of the three pairs of otoliths (lapilli, sagittae, and asterisci) in relation to the swim bladder, which extended forward in close proximity to the sagittae and asterisci. The lappili were the largest otoliths in terms of surface area and volume, but the sagittae were highly modified, appearing spiral in shape when viewed dorsally, with a surface area to volume ratio more than double that of the lapilli. Using scanning electron microscopy, the surface of each otolith was viewable in great detail, and small otoconia (~10.5 μm diameter) were observed on each, but were most numerous on the sagittae. On scanning electron micrographs, the sagittae appeared to be bi‐lobed, with asymmetrical lobes each oriented in the same general direction. Using neutron and X‐ray diffraction methods, we found three polymorphs of calcium carbonate crystals (aragonite, vaterite, and calcite), sometimes all within the same otolith. However, in general, lapilli and sagittae were composed predominately of aragonite whereas asterisci were composed chiefly of vaterite. With these results, we provide information on a unique species, whose inclusion in future studies would benefit our understanding of fish hearing, fish evolution, and fisheries ecology. Abstract : Hiodon alosoides is one of only two extant species within the family Hiodontidae, contained in the Osteoglossomorpha superorder. The morphology and composition of their otoliths indicate unique adaptations that have not been previously described.